AGAMA DAN FILANTROPI: STUDI ATAS PELAYANAN SOSIAL KARINAKAS PERSPEKTIF KARINAKAS - Ita Fitri Astuti (Religi: Jurnal Studi Agama-agama, 2015)
Philanthropy means loving to humanity in the form of giving and constructing socialrelation, including both those of the have and the poor. The basic idea is to supportpublic good and welfare. This article exemplifi es Karinakas, one of the philanthropyinstitutions, that serves as social body under the Diocese Semarang.This institution tries to implement the fairer world order for all, particularly for theweak, the poor, the marginalized and difable. The characteristic of the institutionis social service in health, economy, education and social. Two queries include therelationship between religious understanding and Karinakas’ program and itsconsideration on religious affi liation. The aim of this article is to observe the empiricalfacts applying sociological view with a qualitative descriptive analysis. The researchuses Max Weber’s rationalization in order to respond the inclusive and general typeof Karinakas’ program. In its social outreach, the program is for all regardless of thereligious affi liation. Karinakas has projected its service onto humanity issue.